Membudayakan Literasi Sastra di Era Algoritma, Otomasi, dan Kecerdasan Buatan: Peran Pembelajaran Kreatif di Sekolah - Rizal, Moh Ahsan Shohifur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study examines the development of literary literacy in schools in the era of algorithms, automation, and artificial intelligence, with a focus on the specific role of creative learning. Using a qualitative approach and literature review methods, the study analyzes secondary data from books and journals to identify trends, challenges, and strategies in creative literature learning that utilizes technology. The rapid evolution of technology and the increasing complexity of information highlight the importance of literacy skills in the information age. Cultivating literacy now includes the ability to access, evaluate, and utilize rapidly changing information from diverse sources, as well as navigate the vast amounts of available data. These findings suggest that integrating technology into creative learning can significantly enhance students' reading interest and critical thinking skills. For example, platforms like 1000Kitap and Perusall have been shown to increase reading motivation and facilitate collaborative reading, supporting diverse learners through inclusive pedagogy. However, the study also identifies persistent barriers, such as disparities in technology access and suboptimal digital literacy among students. The rise of misinformation and conspiracy theories online further underscores the importance of information literacy in distinguishing credible sources and combating the spread of false information. Creative learning makes a significant contribution to fostering an adaptive and inclusive literary learning ecosystem in the digital age. This emphasizes the need for innovative and collaborative learning models to address the dynamics of contemporary education. Project-based learning and game-based learning are seen as relevant models that encourage critical thinking, problem-solving, and collaboration by engaging students in real-world projects and interactive game elements. Furthermore, the integration of AI can produce innovative and efficient learning experiences if a balanced approach is adopted that combines AI technology with innovative teaching methods and maintains a continuous focus on research and development. The implications of this research indicate that creative learning is crucial for enriching students' literary literacy and stimulating their creativity in today's complex era